PERKEMBANGAN PENDIDIKAN ISLAM MASA AWAL DI KALIMANTAN - Jeprianto Jeprianto; Bahaking Rama; Muhammad Rusdi Rasyid (ADIBA : JOURNAL OF EDUCATION, 2023)
Islamic education in Kalimantan in its historical trajectory has its own pride, with the publication of a person who received the title "Sun of Islam from Kalimantan". Will the sunshine of education continue to illuminate the footsteps of Islamic education today? Educating the public will be very effective if it starts with integrating with power, Sheikh Arsyad as a scholar who has succeeded in uniting the sultan as the ruling elite and his people on the basis of Islamic teachings, so that there is no separation between the sultan and the people and between the umara and the clergy. This can be achieved because the system of approach that he took went from the bottom, only then to the ruler or sultan.